O ensino de história nos anos iniciais do ensino fundamental - Nascimento, Sandra Regina Luvisetto do (2017)
This dissertation has as its theme the Teaching of History and, as object, the analysis of the theme in the initial years of Elementary School in a school of the state network of the city of São Paulo. They guided the research the following questions: how do the teachers understand the teaching of history in the formation of the children in the initial years? Do the methodological practices developed by them in the classroom contribute to children's awareness? Do the official documents and programs of the public network and the Curriculum Guidelines subsidize a liberating formation in this age group? The theoretical reference that subsidized this work was the conception of liberating education of Paulo Freire. In order to demonstrate the academic and pedagogical relevance of the work, a bibliographical review of the main works, theses and dissertations dealing with this topic was carried out in the Portal of the Coordination of Improvement of Higher Education Personnel (CAPES) and the Brazilian Institute of Information in Science and Technology ( IBICT) as well as a survey on the site of the Scientific Electronic Library Online (Scielo), in the period between 2010 and 2015, in the area of Education. The empirical research was carried out in a public school of the State Network located in the West Zone of the city of São Paulo. In addition to the analysis of the legislative documents, semi-structured interviews were carried out with five teachers from the 1st to 5th grades of the initial years of elementary education. From the examination of the data of the studied reality, it was verified that the discourse on the intentions regarding the teaching of history in this educational cycle differs from the educational practice. Despite the advances of the studies developed in the last decades on the teaching of history, the teaching practice is still linked to a "traditional" format of teaching, based, among other aspects, on the memorization of textbooks and the historical approach decontextualized, impacting Negatively on the idea of training for children's awareness and citizenship.